(untitled) (Bulletin KNOB, 2010)
This article is an adaptation of some reports made between 2005 and 2007 for the art-historical preliminary research into the restorations of the wall paintings in the main church in Breda. In addition, a proposal for restoration is given for the paintings dealt with, emphasizing the preservation of the representations. The first priority in all the paintings is consolidating loose paint and removing dirt from the surface. Subsequently, old putty is removed so as to expose the original painting as much as possible. During the restoration large voids will have to be filled up in a neutral shade – in a lighter shade than the original – so that the distinction between original and restoration remains visible. On the south choir wall in the second bay of the ambulatory at the top three pairs of yellow cloth scissors are painted on a green field (illustration 1). As scissors were an important element in the textile industry, it is plausible that this chapel was painted on the instructions of the cloth guild (illustration 2). The various stages in the production process of the cloth were strictly inspected. These inspections were accompanied by affixing lead seals (illustration 3), which could be considered a full guarantee for the client. Around the scissors in the cloth- scissors chapel in Breda small circles are painted, which were not mentioned in the literature. Although the exact meaning is unknown, these circles could represent lead seals and could thus be a reference to the high quality of the products of the cloth guild in Breda. Both on the second choir pillar at the southside and on the freestanding clustered pillar in the south ambulatory angels with a red cloth of honour are painted (illustration 7, 9 and 10). The former painting dates from approximately 1510-1520 and the latter from the second half of the sixteenth century. It is very likely that the red painted cloth of honour functioned as a background for a sculpture. In miniature art and in painting several examples are known of saints, Mary and Child, the Holy Family and the crucified Christ, placed in front of a cloth of honour. Below the cloth of honour raised by angels on the second choir pillar at the southside is the representation of ‘Separating the sheep from the goats’ (illustration 8). It was probably created between 1540 and 1550. This scene is closely related to ‘The Last Judgement’, as described by Matthew (25: 31-46): ‘(...) And all the peoples will be gathered before Him, and He will separate them from each other, as the shepherd separates the sheep from the goats (...)’. It is a very remarkable representation and as far as I know no other examples of it have been preserved. Usually ‘The Last Judgement’ is represented with Christ as the Judge, sitting on a globe. On the painting in Breda a yellow ball is to be seen, but in view of the fragmentary state of the painting it is not clear whether this is the globe and whether Christ sat on it.